A unique dual sensor for the detection of DCNP (nerve agent mimic) and Cd2+ in water. (21st October 2019) - Ghosh, Ayndrila; Das, Sujoy; Mandal, Saurodeep; Sahoo, Prithidipa
Abstract : A unique carbazole–pyrrole conjugate CPC dual sensor was successfully developed for the simultaneous detection of DCNP (nerve agent mimic) and Cd 2+ – a heavy metal toxicant – in aqueous medium at very low concentrations. Abstract : Both DCNP (nerve gas Tabun mimic) and Cd 2+ are extremely toxic to mankind. We have focused our research on quantitative estimation of DCNP and Cd 2+ in given water samples. A carbazole–pyrrole conjugate CPC has been designed and synthesized which possesses a unique characteristic feature of detecting two hazardous analytes DCNP and Cd 2+ by giving two different optical responses i.e. visual color changes and fluorescence "turn-on" respectively. The PET based chemosensor CPC produces a new compound CPC-1 and a highly fluorescent CPC–Cd 2+ complex upon addition of DCNP and Cd 2+, respectively. The detection limit of CPC for DCNP and Cd 2+ has been estimated to be 7.75 nM and 0.27 μM, respectively, at pH 7.0. Quantum chemical calculations have been executed to demonstrate the electronic properties and the mechanism of the receptor–donor interactions. The concentrations of DCNP and Cd 2+ ions in various water samples have been estimated with the help of standard absorbance and fluorescence curves.